EVALUASI PERTUMBUHAN DAN KELANGSUNGAN HIDUP IKAN PATIN (Pangasius sp.) DALAM BUDIDAYA SKALA MINI MENGGUNAKAN - Septian, Muhammad Faris; Afriansyah, Azmi; Anindita, Atikah Ratna; Fadilla, Agustia Nurul; Chaniago, Izzati Hanifah; Ulfah, Maria; Cahya, Alfiah Dian; Agung (Universitas Sumatera Selatan, 2025)
Catfish (Pangasius sp.) is an important commodity in freshwater aquaculture that has high economic value. This study aims to measure the growth and survival of catfish cultured in a controlled environment using two gallons with different conditions (Gallon A and Gallon B). Results showed that Galon B produced an average absolute length growth of 1.71 cm and an average absolute weight of 2.31 g, higher than Gallon A which reached 0.83 cm and 1.17 g, respectively. Survival rate of fish in Gallon B reached 100%, while in Galon A it was 80%. Factors influencing this difference include water quality, such as temperature, pH, and more optimized rearing management in Gallon B. The temperature ranged from 26-31°C and pH 6. Temperatures ranging from 26-31°C and pH of 6.5-8.7 in Gallon B support better growth and survival. This study emphasizes the importance of water quality management and proper feeding to improve the productivity of catfish farming